ANALISIS PERBANDINGAN TINGKAT KESALAHAN METODE PERAMALAN SEBAGAI UPAYA PERENCANAAN PENGELOLAAN PERSEDIAAN YANG OPTIMAL PADA PT DUTA INDAH SEJAHTERA - Felix Sutisna; Hendy Hendy (Jurnal Bina Manajemen, 2019)
In the manufacturing industry, production planning is very important. Sales forecasting data can be used as a basis for production planning. Good planning allows a company to take the opportunity to sell its products and also has the advantage of competing. In the end to help achieve an optimal decision required the existence of an appropriate management or management, systematic, and can be accounted for. One of the tools that management requires from the decision-making process is the forecasting method. Forecasting method is used to measure or assess the situation in the future. In this study, the authors do the forecasting on the sale of Tessy products Napkin and Non Core types. Forecasting method which author use in this research was Naïve Method, Single Exponential Smoothing, Double Exponential Smoothing, Triple Exponential Smoothing, and Trend Projection. The correct forecasting method for Tessy Napkin and Non Core products is Trend Projection, since Trend Projection has the smallest MAD, MSE, and MAPE levels.